2006
DOI: 10.1242/jcs.02738
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin loss promotes the initiation of squamous cell carcinoma invasion through modulation of integrin-mediated adhesion

Abstract: Much remains to be learned about how cell-cell and cell-matrix interactions are coordinated to influence the earliest development of neoplasia. We used novel 3D human tissue reconstructs that mimic premalignant disease in normal epidermis, to directly investigate how loss of E-cadherin function directs conversion to malignant disease. We used a genetically tagged variant of Ha-Ras-transformed human keratinocytes (II-4) expressing dominant-interfering E-cadherin fusion protein (H-2kd-Ecad). These cells were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…Experimental studies show that changes in cell-cell and cell-matrix adhesion are central to the conversion from premalignant lesions to early invasive carcinoma [13] . Syndecan-1 (CD138) is a member of the transmembrane heparin sulfate proteoglycan (HSPG) family, taking part in and improving adhesion between cell and extracellular matrix [14] , improving cell proliferation, maintaining the differentiation phenotype of cells and inhibiting the growth of tumor cells [15] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies show that changes in cell-cell and cell-matrix adhesion are central to the conversion from premalignant lesions to early invasive carcinoma [13] . Syndecan-1 (CD138) is a member of the transmembrane heparin sulfate proteoglycan (HSPG) family, taking part in and improving adhesion between cell and extracellular matrix [14] , improving cell proliferation, maintaining the differentiation phenotype of cells and inhibiting the growth of tumor cells [15] .…”
Section: Discussionmentioning
confidence: 99%
“…The study of Ohta et al shows that over expression of the homeobox gene HOXD3 promotes the non-expression of E-cadherin and increased expression of integrin β3, which plays an important role in the quick migration and isolation of tumor cells [29] . Zhang et al [11] reported that E-cadherin loss in epithelial tumor progression was not only related to severing cell-cell adhesion but also associated with increased integrins expression, which induced cell-matrix adhesion of these cells [13] . The results of this study indicate that the expressions of syndecan-1 and E-cadherin in gastric tumor tissues are low and their levels are significantly correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…␣ 2 ␤ 1 integrin is a collagen-binding integrin, which engages in various biological functions, including collagen-induced platelet activation and aggregation (31), acting as a mediator for vascular endothelial growth factor-induced angiogenesis (32), and facilitating the invasion and adhesion of squamous cell carcinoma cells (33). The authors of several earlier studies have suggested that the increased level of ␣ 2 ␤ 1 integrin is mediated by the up-regulation of ␣ 2 integrin mRNA abundance (34 -36).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our results suggest that E-cadherin and GnT-III could be regulated by each other in a positive feedback. It has been reported that the association of E-cadherin with ␤1 integrin has an important role in cell-cell adhesion and intracellular signaling (40,41). In order to exclude the possible influence of ␤1 integrin on the regulation of GnT-III, GE11 cells were utilized as our experimental model.…”
Section: Figure 4 Enhanced Expression Of Gnt-iii In Cells Cultured Umentioning
confidence: 99%